2016
DOI: 10.1371/journal.pone.0166897
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma Associated with Xp11.2 Translocation/TFE3 Gene Fusions: Clinical Features, Treatments and Prognosis

Abstract: To investigate the clinical characteristics, treatments and prognosis of renal cell carcinoma associated with Xp11.2 translocation/TFE3 gene fusions (Xp11.2 tRCC), the epidemiological features and treatment results of 34 cases of Xp11.2 tRCC, which were diagnosed by immunohistochemistry staining of TFE3 and fluorescence in situ hybridization at our center, were retrospectively reviewed. The 34 patients included 21 females and 13 males aged 3 to 64 years (median age: 27 years). Four patients were children or ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 32 publications
8
47
0
13
Order By: Relevance
“…Although a prior meta-analysis suggested a female gender predominance in adult XP11.2 translocation RCC [13] , possibly due to its X-chromosome related nature, our study found an equal gender distribution as observed in children which might be explained by the absence of translocation on the Barr body (inactive X chromosome) or by the relatively small number of patients enrolled. Moreover, consistent with previous reports [7,18] and for unknown reasons, right side prevalence was observed in our cohort.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although a prior meta-analysis suggested a female gender predominance in adult XP11.2 translocation RCC [13] , possibly due to its X-chromosome related nature, our study found an equal gender distribution as observed in children which might be explained by the absence of translocation on the Barr body (inactive X chromosome) or by the relatively small number of patients enrolled. Moreover, consistent with previous reports [7,18] and for unknown reasons, right side prevalence was observed in our cohort.…”
Section: Discussionsupporting
confidence: 94%
“…In regard to the risk of disease reoccurrence and death, it is important to conduct prognostic studies to identify potential preoperative risk factors for disease progression and death which might help to guide interventions in the future. Moreover, prognostic researches for adult patients, should be especially encouraged due to at least three reasons: rstly, as a rare disease which mainly affects children [4] , data for adult patients is scarce for the time being which awaits further illumination; secondly, this disease manifests with a more aggressive behavior in adults than in children [3] which suggests a possibly different prognostic features in adults; thirdly, prior prognostic studies, which revealed several possible risk factors as neutrophil-to-lymphocyte ratio (NLR), C-reactive protein/albumin ratio (CRP/Alb ratio), platelet-to-lymphocyte ratio (PLR), tumor stage and inferior vena cava tumor thrombosis, included both child and adult patients [6,7] for analysis which might bring bias. Therefore, it would be of importance to identify novel prognostic factors in adult XP11.2 translocation RCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Результаты FISH-реакции позволили выявить нарушения в области короткого плеча Х-хромосомы (Хр11.2), ассоциированной с транслокацией гена TFE3 (рис. 10) [5]. Ген TFE3 кодирует транскрипционный фактор с основным доменом типа спираль-петля-спираль (Basis-helixloop-helix -bHLH), который связан с IGHM энхансером 3.…”
Section: молекулярно-генетическое исследованиеunclassified
“…RCC in children has higher rates of lymph node and distant metastases than in adults, and up to half of children suffer recurrence after primary surgical resection . Patients with localized tumors at diagnosis have >90% survival after resection, but <15% of patients with Stage 4 disease will survive . The use of adjuvant molecularly targeted therapies, as per NCCN guidelines, is associated with toxicity in adults without durable benefit.…”
Section: Introductionmentioning
confidence: 99%
“…6 Patients with localized tumors at diagnosis have >90% survival after resection, but <15% of patients with Stage 4 disease will survive. 7 The use of adjuvant molecularly targeted therapies, as per NCCN guidelines, 8 is associated with toxicity in adults 9 without durable benefit. Additional therapies are FDA approved for relapsed RCC, but most have limited benefit in adults with median event-free survival of less than 1 year.…”
Section: Introductionmentioning
confidence: 99%